ZbAGL11, a class D MADS-box transcription factor of Zanthoxylum bungeanum, is involved in sporophytic apomixis. (1st February 2021) - Fei, Xitong; Shi, Qianqian; Qi, Yichen; Wang, Shujie; Lei, Yu; Hu, Haichao; Liu, Yulin; Yang, Tuxi; Wei, Anzhi
Abstract: Apomixis is a reproductive model that bypasses sexual reproduction, so it does not require the combination of paternal and maternal gametes but instead results in the production of offspring directly from maternal tissues. This reproductive mode results in the same genetic material in the mother and the offspring and has significant applications in agricultural breeding. Molecular and cytological methods were used to identify the reproductive type of Zanthoxylum bungeanum (ZB). Fluorescence detection of the amplified products of 12 pairs of polymorphic SSR primers showed consistent fluorescence signals for mother and offspring, indicating that no trait separation occurred during reproduction. In addition, the cytological observation results showed differentiation of ZB embryos (2n) from nucellar cells (2n) to form indefinite embryonic primordia and then form adventitious embryos (2n), indicating that the apomictic type of ZB is sporophytic apomixis. The MADS-box transcription factor ZbAGL11 was highly expressed during the critical period of nucellar embryo development in ZB. Unpollinated ZbAGL11 -OE Arabidopsis produced fertile offspring and exhibited an apomictic phenotype. The overexpression of ZbAGL11 increased the callus induction rate of ZB tissue. In addition, the results of the yeast two-hybrid experiment showed that ZbAGL11 could interact with the ZbCYP450 and ZbCAD11 proteins. Our results demonstrate that ZbAGL11 can cause developmental disorders of Arabidopsis flower organs and result in apomixis-like phenotypes.